KEADAAN KESUBURAN KIMIA TANAH PADA TANAH YANG DITANAMI TANAMAN CABAI (Capsicum Annum L) DI DESA LOWIAN KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN - Serliati Ch. Kawengian; Tommy D. Sondakh; Jemmy Najoan (COCOS, 2020)
ABSTRACKThis study was to determine the state of soil chemical fertility in the soil planted withchilies (Capsicum annum L.) in Lowian village, Maesaan District, South Minahasa Regency, aswell as to support chili farming in Lowian village. This research was conducted in Lowianvillage, Maesaan District, South Minahasa Regency. Soil sampling was carried out in twolocations, namely at the top of the village and at the bottom of the village. Furthermore, theanalysis of soil chemical properties at the Laboratory of Chemistry and Soil Fertility, Facultyof Agriculture, Sam Ratulangi University, Manado. The research period starts from Septemberto October 2020. The results of the analysis of several soil chemical properties in chilicultivation in Lowian village, Maesaaan District show that soil acidity (soil pH) is in a slightlyacidic state (6.3 - 6.4), C-organic has a low to moderate content value (1.74). - 2.22), the valueof the cation exchange capacity (CEC) is in a low to moderate state (13.82 - 18.54), Nitrogennutrient content is low (0.14 - 0.19), Phosphorus nutrient content is in a low state (11.64 -12.45), and the nutrient content of Potassium is in a low state (13.32 - 20.11) In general, basedon the results of laboratory analysis, it was stated that the soil chemical fertility in Lowianvillage, Maesaaan District, was at a low level.Key words: Soil, chemical properties, chili plants